Incidence of Various Causes of Stillbirth in Pakistan: A Cross-Sectional Study - Tahmina Mahar, Madhu Bala, Nadira Kasi, Sana Umer Arain, Shazia Ramzan, Naseeb Nama, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The present study aims to explore different factors linked with this stillbirth rate in Pakistan, which are; sociodemographic factors, living experiences, and health-related factors related to this highest stillbirth rate, and reflect their relationship with the pregnancy, birth elements, and stillbirth in the context of tertiary healthcare setting in Pakistan. Study design: A cross-sectional study Place and Duration: This was a multicentric study which was conducted at Unit II Ghulam Muhammad Mahar Medical College Teaching Hospital Sukkur, Civil Hospital Quetta and Muhammad Medical and Dental College Mirpurkhas from March 2021 to March 2022. Methodology: This study gathered data related to respondent demographics and their clinical history. For the stillbirth data, this study uses fitted bi-variable and multivariable models with two options, yes/no, and three categories, i.e., mothers' livebirth/macerated/non-macerated stillbirth. This method explores and identifies their linkage with the respondents' demographic and clinical aspects. Results: Results show that there were, in total, 1999 neonates and 1927 mothers as the sample size. Findings show that the increased odds of stillbirth were linked with maternal inadequate education, distancing issue, people living in huts or cottages, hypertensive mothers, history of stillbirth, complexities with birth, increased time for labor, antepartum hemorrhage, long hours of labor or obstructed labor, vaginal breech at the time of delivery, cesarean in an emergency condition and signs of the trauma after birth to the neonate. Conclusion. The results show that some factors responsible for stillbirth can be used to develop interventions needed to improve Pakistan's public health conditions. Eventually, it will reduce preventable deaths and improve the condition of maternal health in that particular region. Keywords: Stillbirth, Maternal health, Avoidable death, universal health.